New Eocene Coleoid (Cephalopoda) Diversity from Statolith Remains: Taxonomic Assignation, Fossil Record Analysis, and New Data for Calibrating Molecular Phylogenies - Neige, Pascal; Lapierre, Hervé; Merle, Didier (PLOS ONE, 2016)
New coleoid cephalopods are described from statolith remains from the Middle Eocene (Middle Lutetian) of the Paris Basin. Fifteen fossil statoliths are identified and assigned to the Sepiidae (Sepia boletzkyi sp. nov.,? Sepia pira sp. nov.), Loliginidae (Loligo clarkei sp. nov.), and Ommastrephidae (genus indet.) families. The sediments containing these fossils indicate permanent aquatic settings in the infralittoral domain. These sediments range in age from 46 Mya to 43 Mya. Analysis of the fossil record of statoliths (from findings described here, together with a review of previously published data) indicates marked biases in our knowledge. Fossil statoliths are known from as far back as the Early Jurassic (199.3 to 190.8 Mya) but surprisingly, to the best of our knowledge, no record occurs in the Cretaceous. This is a “knowledge bias” and clearly calls for further studies. Finally, we attempt to compare findings described here with fossils previously used to constrain divergence and/or diversification ages of some coleoid subclades in molecular phylogenies. This comparison clearly indicates that the new records detailed here will challenge some estimated divergence times of coleoid cephalopod subclades.